The association between inflammatory and immune system biomarkers and the dietary inflammatory index in patients with COVID-19 - Barania Adabi, Somayyeh; Daneghian, Sevana; Khalkhali, Hamidreaza; Nejadrahim, Rahim; Shivappa, Nitin (Frontiers in Nutrition, 2023)
Background Inflammation and cytokine storm have been reported to be the main cause of acute symptoms of coronavirus disease (COVID-19). Diet-induced inflammation may affect the condition of patients with COVID-19. Therefore, this study aimed to investigate the relationship between disease severity, inflammatory and immune system biomarkers, and the dietary inflammatory index (DII) in patients with COVID-19. Methods This cross-sectional study was conducted on 500 adult patients with COVID-19. Patients were divided into mild, moderate, and severe conditions based on clinical and laboratory evidence. A validated food frequency questionnaire (FFQ) was used to determine DII and energy-adjusted DII (E-DII) scores. The serum C-reactive protein (CRP) level and blood cell count were measured for all patients. Multiple linear regression was used to explore the association between DII and E-DII and CRP, blood cell counts, and hospitalization in patients with COVID-19. Results Coronavirus disease (COVID-19) patients with higher DII had higher consumption of fat and carbohydrate and lower intakes of protein, anti-inflammatory nutrients, garlic, caffeine, tea, onion, and fiber (P < 0.05). There was a positive association between DII and CRP (β = 1.024, P < 0.001), hospitalization (β = 1.062, P < 0.001), WBC count (β = 0.486, P < 0.009), neutrophil count (β = 0.565, P < 0.001), and neutrophil-to-lymphocyte ratio (β = 0.538, P < 0.001) and a negative association between DII and the lymphocyte count (β = −0.569, P < 0.001). There was a positive association between E-DII and hospitalization (β = 1.645, P < 0.001), WBC count (β = 0.417, P < 0.02), and neutrophil-to-lymphocyte ratio (β = 0.35, P < 0.03). Conclusion There is a positive correlation between DII and inflammation, immune hyperactivation, and length of hospital stay in patients with COVID-19. Further longitudinal studies are necessary.